Characterization and analysis on the hemispherical point temperature uncertainty problem of mold flux with volatiles - Wang, Ze; Ren, Mengmeng; Zhao, Junxue; Zhang, Zhenkai; Wang, He; Hu, Ailin; Cui, Yaru (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
In hemisphere point temperature (Thp) measurement of continuous casting mold flux, the evaporation of volatiles under high temperature will have a strong impact on the results. Based on the comprehensive analysis of hemisphere point method and its influencing factors, the corresponding volatile-containing mold flux and non-volatile mold flux were selected to get Thp with different heating rates. Combined with the Thp measurement and TG-DSC results, the effect of relevant factors during measuring process were analysed and the way to characterize and evaluate the effects were suggested. Furthermore, an improved method of mold flux melting point test was put forward. The results showed that for non-volatile mold flux, the temperature hysteresis has a greater effect than heat transfer delay and fractional melting. And for mold flux with volatile, the effect of evaporation is greater than other factors. Traditional hemisphere-point method is no longer suitable for the volatile mold flux. In order to get through this problem, improved methods were proposed. One is measuring Thp by traditional way, correcting the composition at the Thp, corresponding Thp with the corrected composition. Another is taking the initial composition, revising the hemispherical point temperature Thp, matching the revised Thp with the initial composition.